Reliably detecting snowshoe hares with winter track counts - David M. Burt; Gary J. Roloff; Dwayne R. Etter; Eric Clark (Wildlife Society Bulletin)
ABSTRACT We determined the optimum transect length and spacing for detecting snowshoe hare (Lepus americanus) from snow‐track surveys in a fixed area. We also evaluated the utility of the most reliable and efficient designs for indexing hare density. We constructed enclosures (∼6.1 ha) at 2 locations in the Upper Peninsula of Michigan, USA, and populated the enclosures with radiocollared hares. Hare densities ranged from 0.2 to 1.5 hares/ha in the enclosures, comparable to low and high densities recorded at the southern extent of snowshoe hare range. During winters of 2012–2014, we conducted snow‐track surveys along 9 transects spaced 25 m apart in the enclosures 12–65 hr after a snowfall and mapped the location of every track that intersected a transect. After standardizing the track maps by time since last snowfall, we simulated different transect lengths and spacing and evaluated whether hares were documented on the resultant transect segments. We deemed transect configurations reliable if >90% of the 10,000 simulations correctly denoted the site as occupied. Of the 28 possible transect configurations, only 10 combinations were found to reliably detect hares. We refined the 10 reliable configurations based on efficiency, where efficiency was based on the distance traversed by a surveyor. We recommend using transects that are 150 m in length with 100‐m or 75‐m spacing, or 125 m in length with 75‐m spacing to reliably and efficiently survey a fixed area for snowshoe hares. © 2016 The Wildlife Society.